FREQUENCY OF FMS-LIKE TYROSINE KINASE 3 KINASE DOMAIN POINT MUTATION (FLT3/TKD MUTATION) IN DIFFERENT AGE GROUPS OF ACUTE MYELOID LEUKEMIA PATIENTS. - Khaleeq unnisa; zeeshan ulqadar; sadaf shahab; Muhammad Nadeem; Danish Zahid; zaen ulAbedin; Saqib Ansari; Tasneem Farzana; Mehwesh Taj; Munira Borhany; Arshi Naz; Tahir Sultan Shamsi (Mediterranean Journal of Hematology and Infectious Diseases)
Activation of the FLT3 receptor tyrosine kinase, by point mutations in the second tyrosine kinase domain (TKD), has been described in patients with acute myeloid leukemia (AML). This study was planned to estimate the frequency of FMS-like Tyrosine Kinase 3 Kinase Domain Point Mutation (FLT3/TKD Mutation) D835Y via PCR in different age groups of AML patients. An observational cross sectional study was carried out in National Institute of Blood Diseases and Bone Marrow Transpalntation (NIBD) from May 2010 to October 2011. AML patients diagnosed on the basis of WHO classification of myeloid neoplasms 2008 were included in the study. PCR was used to detect FLT 3/ TKD mutation (D835Y) from peripheral blood samples. DNA was extracted and  exon 20  was amplified using primers 20F and 20R. Eco RV restriction enzyme was used to discriminate between mutant D835Y and the wild type followed by 2%   agarose gel electrophoresis. A small cohort of cytogenetically unsolicited 151 AML patients were analysed. D835Y mutation was detected in 15 (9.9%) out of 151 patients. D835Y mutation was more frequent approximately double in men (12.1%) than in women (6.7%). The frequency of D835Y mutation increased above 60 years; 2 (14.3%) out of total 14 cases had the mutation in this age group. D835Y mutations were more prevalent in patients with Acute myelomonocytic leukemia  (17.6%) followed by AML with maturation (14.9%). In conclusion, FLT3/ TKD mutation has been detected in 9.9% cases of AML patients. It is more commonly seen in male, at increased age and in Acute myelomonocytic leukaemia. Keywords: Acute myeloid leukemia (AML), FLT3, TKD mutation, NIBD, Pakistan